ESTIMATING THE DEMAND FUNCTION OF RICE PRODUCTION IN NIGERIA (1981 – 2018) - Amalu Emeka Melvin; Uzoigwe Amara (Universitas PGRI Madiun, 2022)
The study estimated the demand function for rice in Nigeria from 1981 to 2018. The objective was to estimate the short run and long run demand function (including price elasticities) of rice in Nigeria from 1981 to 2018. Secondary time series data were used for the study. The data were analyzed using inferential statistics of which the Johansen Maximum likelihood method of cointegration was used. The results revealed that the previous years’ demand (0.353) and price of close substitute (0.182) significantly affected demand in the short-run with an ECM (-1) of -0.653 while for long run price of close substitute (0.118), population (1.68) and policy (-0.186) affects demand. The results also showed that the price elasticity of rice demand in the long-run and short-run were -0.033 and -0.093 and were both non-significant at 5 percent level. The demand for rice is price inelastic.. It was recommended that adequate policy framework aimed at increasing supply of local rice should be pursued as this will reduce the prices of local rice brands and invariably enhance demand for local rice by households as rice was estimated to be own price inelastic